2017
DOI: 10.7717/peerj.3302
|View full text |Cite
|
Sign up to set email alerts
|

Body composition estimation from selected slices: equations computed from a new semi-automatic thresholding method developed on whole-body CT scans

Abstract: BackgroundEstimating volumes and masses of total body components is important for the study and treatment monitoring of nutrition and nutrition-related disorders, cancer, joint replacement, energy-expenditure and exercise physiology. While several equations have been offered for estimating total body components from MRI slices, no reliable and tested method exists for CT scans. For the first time, body composition data was derived from 41 high-resolution whole-body CT scans. From these data, we defined equatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 36 publications
0
21
0
Order By: Relevance
“…It has been shown that CT scan slices located at the waist level are the most efficient way to estimate total body components mass or volumes when those cannot be directly estimated with whole‐body based techniques (Kvist, Chowdhury, Grangard, Tylen, & Sjöström, ; Lacoste Jeanson et al, ; Lemieux, Lesage, & Bergeron, ; Mourtzakis et al, ). We estimated total body FM and FFM, and calculated the resulting body fat percentage (BF%) from these data, using a new set of regression equations from a slice located between the 4th and 5th lumbar vertebrae (Lacoste Jeanson et al, ). The cross‐validation test for those equations showed absolute prediction errors not greater than ± 3.67 kg for FFM, and 1.71 kg for FM by individual (Lacoste Jeanson et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that CT scan slices located at the waist level are the most efficient way to estimate total body components mass or volumes when those cannot be directly estimated with whole‐body based techniques (Kvist, Chowdhury, Grangard, Tylen, & Sjöström, ; Lacoste Jeanson et al, ; Lemieux, Lesage, & Bergeron, ; Mourtzakis et al, ). We estimated total body FM and FFM, and calculated the resulting body fat percentage (BF%) from these data, using a new set of regression equations from a slice located between the 4th and 5th lumbar vertebrae (Lacoste Jeanson et al, ). The cross‐validation test for those equations showed absolute prediction errors not greater than ± 3.67 kg for FFM, and 1.71 kg for FM by individual (Lacoste Jeanson et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…We estimated total body FM and FFM, and calculated the resulting body fat percentage (BF%) from these data, using a new set of regression equations from a slice located between the 4th and 5th lumbar vertebrae (Lacoste Jeanson et al, ). The cross‐validation test for those equations showed absolute prediction errors not greater than ± 3.67 kg for FFM, and 1.71 kg for FM by individual (Lacoste Jeanson et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Body composition was measured using CT during the procedure and at terminal follow‐up, according to established methods . Specifically, from each procedure image set, an axial section that crossed the L1 center was identified.…”
Section: Methodsmentioning
confidence: 99%
“…To test the efficiency of both the Extractor and Diaphysator, we used a sample of whole‐body CT scans performed on cadavers at the University of Copenhagen, Department of Forensic Medicine, Unit of Forensic Anthropology in Copenhagen, Denmark (Lacoste Jeanson, Dupej, et al, ; Lacoste Jeanson, Santos, et al, ; Villa et al, ). The bodies have not been positioned in a standardized fashion prior to scanning.…”
Section: Case Studymentioning
confidence: 99%
“…The sample consists of 36 males and 42 females. Full descriptive data of the sample can be found elsewhere (Lacoste Jeanson, Dupej, et al, ; Lacoste Jeanson, Santos, et al, ; Villa et al, ). The full data, along with those of the tibial diaphysis, are publicly available on Zenodo (Lacoste Jeanson, ) or by clicking the “Help” button in the Diaphysator user interface.…”
Section: Case Studymentioning
confidence: 99%